PENGARUH PERILAKU BULLYING TERHADAP KESEHATAN MENTAL PESERTA DIDIK SEKOLAH MENENGAH ATAS NEGERI 2 BATANG KAPAS - Wahyu, Rahma Vilka; Suryadi, Suryadi; Solina, Wira (STKIP Pesisir Selatan, 2025)
This research is based on a phenomenon in the field, namely there are still students who are afraid to go to school, and there are students who are quiet and like to be alone, and there are students who are unable to adapt to the surrounding environment. The objectives of this study are 1) The mental health of SMAN 2 Batang Kapas students, 2) The effect of bullying of SMAN 2 Batang Kapas students, 3) The effect of bullying behavior on the mental health of SMAN 2 Batang Kapas students. This study uses a correlational quantitative research method. The population of this study is 30 people. The sampling technique uses total sampling. The instrument used in this study is a questionnaire. The data analysis in this study is percentage and simple linear regression. Based on the research, the following results were obtained: 1) Bullying behavior of students is in the very low category, 2) Mental health of students is in the low category 3) There is a significant influence between bullying behavior on mental health at SMAN 2 Batang Kapas, which is 15.9%. Based on the results of this study, the researcher recommends to guidance and counseling teachers to continue to develop guidance programs that support the formation of students' character and behavior through appropriate approaches, and also recommend to students to increase confidence and the importance of mental health.